Republic of Congo : 2007 Article IV Consultation; Staff Report; Staff Statement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for the Republic of Congo. (IMF Staff Country Reports; Country Report ;, 2007)
This 2007 Article IV Consultation highlights that the implementation of the Poverty Reduction and Growth Facility (PRGF)-supported program was broadly satisfactory for Congo in 2004-05. However, expenditure overruns and delays in structural reforms pushed the program off track in 2006. Discussions are continuing on an IMF staff-monitored program aimed at establishing a solid track record that could pave the way for resuming discussions on the PRGF-supported program. Macroeconomic performance was mixed in 2006. Real GDP growth is estimated at 6.1 percent in 2006. The outlook for 2007 and the medium term is uncertain.